Citraan dalam Kumpulan Puisi Sehimpun Puisi (Ikan-Ikan Kebaikan Terbang, Dari Sungai Ke Langit Lengang) Karya Muhammad Aqalani Eneste) - Rahayu, Sri; Nur, Hidayatun; Raizaqi, Mhd (UIR Press, 2026)
This research is motivated by the importance of imagery in a literary work, especially poetry. This study aims to describe, analyze, and interpret the imagery in a collection of poems Sekumpul Puisi (The fish of goodness fly, from the river to the deserted sky) by Muhammad Asqalani Eneste. The method used in this study is a descriptive method with a qualitative approach, the data source in this study is a collection of poems Sekumpul Puisi (The fish of goodness fly, from the river to the deserted sky) by Muhammad Asqalani Eneste. The data collection technique in this study uses hermeneutic techniques, through the following steps: 1. Classifying data according to research problems, 2. Analyzing data with the theory of imagery proposed by Herman Waluyo (2005). After analyzing the data, the results of the study were found regarding the imagery in the Collection of Poems Sekumpul Puisi (The fish of goodness fly and the river to the deserted sky) by Muhammad Asqalani Eneste. The collection of poems illustrates the quality of poetry and the crucial role of imagery in poetry, as the poet uses language to evoke imagination and ideas in the reader's mind through the use of the five senses as a means of representation. The poetry collection by Muhammad Asqalani Eneste contains 74 visual images and 9 poems, 1 tactile image and 9 poems, and 5 visual images and 9 poems.